Tetrahedral global minimum for the 98-atom Lennard-Jones cluster. - Leary, R; Doye, J (1999)
An unusual atomic cluster structure corresponding to the global minimum of the 98-atom Lennard-Jones cluster has been found using a variant of the basin-hopping global optimization algorithm. The structure has tetrahedral symmetry and an energy of -543.665 361 epsilon, which is 0.022 404 epsilon lower than the previous lowest-energy minimum. The LJ(98) structure is of particular interest because its tetrahedral symmetry establishes it as one of only three types of exception to the general pattern of icosahedral structural motifs for optimal LJ microclusters. Similar to the other exceptions the global minimum is difficult to find because it is at the bottom of a narrow funnel that only becomes thermodynamically most stable at low temperature.